2008
DOI: 10.1007/s10384-008-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation on IGF-1 transcription by L-type calcium channels in cultured retinal Müller cells

Abstract: These results indicate that the enhancement of IGF-1 transcription by ES in cultured Müller cells depends largely on Ca(2+) influx through L-type Ca(2+) channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 21 publications
5
53
0
Order By: Relevance
“…It has been suggested that TES increases the number of surviving RGCs in vivo, probably because of increased levels of IGF-1 produced by Müller cells. 24,58 Another study demonstrated that the expression of mRNA encoding brain-derived neurotrophic factor increased and that intracellular protein levels were found in cultured Müller cells after TES, 59 supported by Ni et al 26 The last study also demonstrated that the levels of ciliary nerve trophic factor and expression of Bcl-2 were both increased after TES. 26 In cultured retinal Müller cells, Sato et al 60 showed that TES also increased the expression of fibroblast growth factor 2, which was also BCVA, best-corrected visual acuity; BVMD, best vitelliform macular dystrophy; CRD, cone-rod dystrophy; DTL, Dawson-Trick-Litzkow; EEPR, electrically evoked pupillary response; EPT, electrical phosphene threshold; ERG, electroretinogram; ES, electrical stimulation; FDG, 18 F-fluorodeoxyglucose; HFA, Humphrey field analyzer; IOP, intraocular pressure; LSFG, laser speckle flowgraphy; mfERG, multifocal electroretinogram; NAION, nonarteritic ischemic optic neuropathy; PET, positron emission tomography; POAG, primary open-angle glaucoma; PR, pupillary reflex; RAO, retinal artery occlusion, RD, retinal degeneration; RP, retinitis pigmentosa; SBR, square blur rate; STG, Stargardt disease; TES, transcorneal electrical stimulation; TON, traumatic optic neuropathy; VA, visual acuity; VF, visual field; e, not reported.…”
Section: Possible Mechanisms Underlying the Effects Of Esmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been suggested that TES increases the number of surviving RGCs in vivo, probably because of increased levels of IGF-1 produced by Müller cells. 24,58 Another study demonstrated that the expression of mRNA encoding brain-derived neurotrophic factor increased and that intracellular protein levels were found in cultured Müller cells after TES, 59 supported by Ni et al 26 The last study also demonstrated that the levels of ciliary nerve trophic factor and expression of Bcl-2 were both increased after TES. 26 In cultured retinal Müller cells, Sato et al 60 showed that TES also increased the expression of fibroblast growth factor 2, which was also BCVA, best-corrected visual acuity; BVMD, best vitelliform macular dystrophy; CRD, cone-rod dystrophy; DTL, Dawson-Trick-Litzkow; EEPR, electrically evoked pupillary response; EPT, electrical phosphene threshold; ERG, electroretinogram; ES, electrical stimulation; FDG, 18 F-fluorodeoxyglucose; HFA, Humphrey field analyzer; IOP, intraocular pressure; LSFG, laser speckle flowgraphy; mfERG, multifocal electroretinogram; NAION, nonarteritic ischemic optic neuropathy; PET, positron emission tomography; POAG, primary open-angle glaucoma; PR, pupillary reflex; RAO, retinal artery occlusion, RD, retinal degeneration; RP, retinitis pigmentosa; SBR, square blur rate; STG, Stargardt disease; TES, transcorneal electrical stimulation; TON, traumatic optic neuropathy; VA, visual acuity; VF, visual field; e, not reported.…”
Section: Possible Mechanisms Underlying the Effects Of Esmentioning
confidence: 89%
“…The American Journal of Pathology -ajp.amjpathol.org 58,59 In primary microglia isolated from retinas of SpragueDawley rats, the inhibitory effects of ES on the secretion of IL-1b and tumor necrosis factor-a were confirmed, as well as favorable effects on the production of brain-derived neurotrophic factor and ciliary nerve trophic factor in Müller cells 35 and the down-regulation of the proapoptopic gene Bax. 26 Willmann et al 34 also showed that TES led to clear changes in the expression of neuroprotective genes and that different genes may be expressed, depending on whether TES was applied to a healthy or diseased retina.…”
Section: Improving Vision By Electrostimulationmentioning
confidence: 90%
“…[35][36][37] In animal experiments electrical stimulation has been shown to be beneficial for the survival of photoreceptors in Royal College of Surgeon's (RCS) rats, 38 to rescue ganglion cells after optic nerve injury 39,40 and to preserve retinal cells after light-induced retinal damage (Zhang H, et al IOVS 2009;50:ARVO E-Abstract 3615). 41 The neuroprotective effects of electrical stimulation have been attributed to upregulation of growth factors, such as insulin-like growth factor-1 (IGF-1), 39,42 fibroblast growth factor-2 (FGF-2), 34,43 ciliary neurotrophic factor (CNTF), 44,45 brain-derived neurotrophic factor (BDNF), 41,46 and to overexpression of neuroprotective genes, such as B-cell lymphoma-2 (BCL-2), 47 BAX, or some tumor necrosis factor genes.…”
Section: Resultsmentioning
confidence: 99%
“…15 In animals, a protective effect of TES has been described for ischemic rat retinas by Wang et al 16 Moreover, Morimoto et al 17 have shown an increased survival of axotomized retinal ganglion cells, which has been confirmed by Okazaki et al 18 The effect of TES has been attributed to the release of neurotrophic factors, 5 such as an increased expression of insulin-like growth factor (IGF-1), [19][20][21] brain-derived neurotrophic factor (BDNF), 6,22,23 FGF2, 24 and B-cell lymphoma 2 protein. 25 Protective effects of TES have also been linked to the downregulation of pro-apoptotic factors, such as BAX and tumor necrosis factors, 25 which are involved in the apoptosis cascade of retinal cells.…”
Section: Discussionmentioning
confidence: 64%
“…57 Another pathway may be via the increased expression of IGF-1 after TES. [19][20][21] Also, a potential effect of TES on activator protein 1 regulation, which has been shown to be an initiator of photoreceptor degeneration in light damage, 35,69 may be involved. It seems likely that TES induces a variety of beneficent neuroprotective regulators, but further studies are still needed to clarify definite protective pathways.…”
Section: Protective Mechanismsmentioning
confidence: 99%